1998
DOI: 10.1023/a:1005905723550
|View full text |Cite
|
Sign up to set email alerts
|

Antisense depletion of RIα subunit of protein kinase A induces apoptosis and growth arrest in human breast cancer cells

Abstract: In recent years, several laboratories have explored the possibility of using antisense oligodeoxynucleotides for specific manipulation of gene expression leading to cancer treatment. The enhanced expression of the RIalpha subunit of cyclic AMP-dependent protein kinase type I (PKA-I) has been correlated with cancer cell growth. In the present study, the effects of an antisense oligodeoxynucleotide targeted against RIalpha subunit of PKA-I on growth inhibition and apoptosis in MDA-MB-231 human breast cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…These molecular effects were consistent with the growth inhibition and the reverted phenotype observed in transformed cells treated with these ODNs (20)(21)(22)(23)(24). Importantly, the cluster analysis observed in the absence (Fig.…”
Section: Tumor-specific Expression Signature and Reverse Transformationsupporting
confidence: 83%
“…These molecular effects were consistent with the growth inhibition and the reverted phenotype observed in transformed cells treated with these ODNs (20)(21)(22)(23)(24). Importantly, the cluster analysis observed in the absence (Fig.…”
Section: Tumor-specific Expression Signature and Reverse Transformationsupporting
confidence: 83%
“…The RIa antisense oligodeoxynucleotide seemed to restrain tumor cell growth by inhibiting tyrosine kinase signaling, cell cycle deregulation, and induction of apoptosis and differentiation (25, 36 -40). Treatment with RIa antisense of different types of cancer cell lines (MCF-7 hormone dependent, MDA-MB-231 hormone-independent breast cancer, PC3M hormoneinsensitive prostate cancer) induces growth inhibition through apoptotic pathway (25,38,40). Along with these data, our present study shows that antisense RIa inhibits HCT-15 multidrug resistant tumor growth in nude mice involving modulation of apoptotic proteins, such as Bcl-2, Bax, and Bak.…”
Section: Discussionsupporting
confidence: 76%
“…Initially, 8-Cl-cAMP was reported to inhibit cancer cell proliferation without inducing cell death (10). However, recent reports showed that 8-Cl-cAMP induces apoptotic cell death as well in cancer cells (24,25). Therefore, we assumed that both the inhibition of cell proliferation and the apoptotic cell death may constitute 8-Cl-cAMP-induced growth inhibition.…”
Section: Discussionmentioning
confidence: 94%